Effect of extracranial lesion severity on outcome of endovascular thrombectomy in patients with anterior circulation tandem occlusion: analysis of the TITAN registry. (6th March 2019) - Anadani, Mohammad; Spiotta, Alejandro; Alawieh, Ali; Turjman, Francis; Piotin, Michel; Steglich-Arnholm, Henrik; Holtmannspötter, Markus; Taschner, Christian; Eiden, Sebastian; Haussen, Diogo C; Nogueira, Raul; Papanagiotou, Panagiotis; et al.
Abstract : Introduction: Endovascular treatment (EVT) for tandem occlusion (TO) of the anterior circulation is complex but effective. The effect of extracranial internal carotid artery (EICA) lesion severity on the outcomes of EVT is unknown. In this study we investigated the effect of EICA lesion severity on the outcomes of tandem occlusion EVT. Methods: A multicenter retrospective TITAN (Thrombectomy In TANdem lesions) study that included 18 international endovascular capable centers was performed. Patients who received EVT for atherosclerotic TO with or without EICA lesion intervention were included. Patients were divided into two groups based on the EICA lesion severity (high-grade stenosis (≥90% North American Symptomatic Carotid Endarterectomy Trial) vs complete occlusion). Outcome measures included the 90-day clinical outcome (modified Rankin Scale score (mRS)), angiographic reperfusion (modified Thrombolysis In Cerebral Ischemia (mTICI) at the end of the procedure), procedural complications, and intracranial hemorrhage at 24 hours follow-up. Results: A total of 305 patients were included in the study, of whom 135 had complete EICA occlusion and 170 had severe EICA stenosis. The EICA occlusion group had shorter mean onset-to-groin time (259±120 min vs 305±202 min; p=0.037), more patients with diabetes, and fewer with hyperlipidemia. With respect to the outcome, mTICI 2b–3 reperfusion was lower in the EICA occlusion group (70% vs 81%; p=0.03). The favorable outcome (90-day mRS 0–2), intracerebral hemorrhage and procedural complications were similar in both groups. Conclusion: Atherosclerotic occlusion of the EICA in acute tandem strokes was associated with a lower rate of mTICI 2b–3 reperfusion but similar functional and safety outcomes when compared with high-grade EICA stenosis.